2022
DOI: 10.2147/jir.s372773
|View full text |Cite
|
Sign up to set email alerts
|

Punicalagin Attenuates LPS-Induced Inflammation and ROS Production in Microglia by Inhibiting the MAPK/NF-κB Signaling Pathway and NLRP3 Inflammasome Activation

Abstract: Purpose Neurodegenerative diseases are associated with neuroinflammation along with activation of microglia and oxidative stress, but currently lack effective treatments. Punicalagin is a natural bio-sourced product that exhibits anti-inflammatory effects on several chronic diseases; however, the anti-inflammatory and anti-oxidative effects on microglia have not been well examined. This study aimed to investigate the effects of punicalagin on LPS-induced inflammatory responses, NLRP3 inflammasome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…Jung Lo et al were able to demonstrate that pretreatment with punicalagin of LPS-treated murine BV2 microglia cells attenuated inflammation with a reduction in the secretion of the pro-inflammatory cytokines iNOS, IL-1β, and IL-6. There was also a decrease in NF-κB activity and inhibition of NLRP3 activation [209]. The antioxidant properties of punicalagin are known.…”
Section: Punicalaginmentioning
confidence: 96%
See 1 more Smart Citation
“…Jung Lo et al were able to demonstrate that pretreatment with punicalagin of LPS-treated murine BV2 microglia cells attenuated inflammation with a reduction in the secretion of the pro-inflammatory cytokines iNOS, IL-1β, and IL-6. There was also a decrease in NF-κB activity and inhibition of NLRP3 activation [209]. The antioxidant properties of punicalagin are known.…”
Section: Punicalaginmentioning
confidence: 96%
“…Indeed, it is known to scavenge 2,2-diphenyl-1picrylhydrazyl radical (DPPH) and hydrogen peroxide H 2 O 2 [210,211]. It is also known to decrease the production of intracellular and mitochondrial ROS [209]. Furthermore, punicalagin enhances Nrf2 and HO-1 expression in RAW264.7 macrophages, where oxidative stress was induced by LPS.…”
Section: Punicalaginmentioning
confidence: 99%
“…1F , treatment with lipofundin in the concentration range of 62.5-250 µg/ml significantly reduced NO production compared with that in cells treated with LPS alone, with the maximal anti-inflammatory effect observed at a concentration of 125 µg/ml. During the activation of BV2 cells, NOS2 expression is highly upregulated, leading to the generation of a large amount of NO ( 13 ). To evaluate the activation status of BV2 cells, the expression of NOS2 was assessed using western blot analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Xu et al found that the phosphorylation of STAT3 contributed to PU‐induced HO‐1 expression during M2c phenotype polarization (Xu et al, 2017). Lo et al demonstrated that PU reduces the secretion of IL‐6 and inhibits the phosphorylation of STAT3 in LPS‐induced BV2 cells (Lo et al, 2022). Our results showed that PU inhibits the phosphorylation of p65 and ERK1/2 in a time‐ and dose‐dependent manner in HEKa and HaCaT cells.…”
Section: Discussionmentioning
confidence: 99%